IRF6 mutation screening in non‐syndromic orofacial clefting: analysis of 1521 families. Issue 1 (1st October 2015) - Leslie, E.J.; Koboldt, D.C.; Kang, C.J.; Ma, L.; Hecht, J.T.; Wehby, G.L.; Christensen, K.; Czeizel, A.E.; Deleyiannis, F.W.‐B.; Fulton, R.S.; Wilson, R.K.; Beaty, T.H.; et al.
Abstract : Van der Woude syndrome (VWS) is an autosomal dominant malformation syndrome characterized by orofacial clefting (OFC) and lower lip pits. The clinical presentation of VWS is variable and can present as an isolated OFC, making it difficult to distinguish VWS cases from individuals with non‐syndromic OFCs. About 70% of causal VWS mutations occur in IRF6, a gene that is also associated with non‐syndromic OFCs. Screening for IRF6 mutations in apparently non‐syndromic cases has been performed in several modestly sized cohorts with mixed results. In this study, we screened 1521 trios with presumed non‐syndromic OFCs to determine the frequency of causal IRF6 mutations. We identified seven likely causal IRF6 mutations, although a posteriori review identified two misdiagnosed VWS families based on the presence of lip pits. We found no evidence for association between rare IRF6 polymorphisms and non‐syndromic OFCs. We combined our results with other similar studies (totaling 2472 families) and conclude that causal IRF6 mutations are found in 0.24–0.44% of apparently non‐syndromic OFC families. We suggest that clinical mutation screening for IRF6 be considered for certain family patterns such as families with mixed types of OFCs and/or autosomal dominant transmission.